Determination of parvovirus antibodies in canine serum using magnetic bead‐based chemiluminescence immunoassay - Chen, Cuicui (Biotechnol Appl Biochem, 2019)
Canine parvovirus type 2 (CPV‐2), as a highly contagious and potentially fatal disease of dogs and many other carnivores, usually causes severe gastroenteritis and myocarditis. Therefore, it is very necessary and urgent to have an accurate method to determine the CPV‐2 antibodies (CPV‐2‐Ab) in canine samples. Here, a magnetic bead–based chemiluminescence immunoassay was established and optimized to detect the concentration of CPV‐2‐Ab in serum. And a commercial assay was also used to evaluate the consistency with our method. After optimization of the detective system, the CPV‐2‐Ab was captured by CPV‐antigen‐magnetic bead (8.3 µg/mL); then combined with the conjugation of anti‐canine IgG antibody‐acridinium ester (0.36 µg/mL). Finally, collected the signal (read the luminosity) after 1 H reaction time. The linear correlation coefficient (R(2)) is 0.9924. The limit of detection (sensitivity) is 0.36 ng/mL (the linear dynamic range: 1.32–93.75 ng/mL), and the average recovery is 100.89% without cross‐reactions with other canine viral antibodies. The results’ correlation between commercial assays and this method is 0.9888. This immunoassay establishes that it has high sensitivity, accuracy, and specificity in clinical analysis, indicating that this method could be suitable for quantitative detection of CPV‐2‐Ab and evaluation of vaccination effect.